Analisys of financial performance by regions of Colombia: 2009-2012: an approach of territorial competitiveness evaluation - Castaño Ríos, Carlos Eduardo; Arias Pérez, José Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The aim of this paper is to present the financial performance evaluation of business by region in Colombia for the period 2009-2012, from the comprehensive financial analysis, with a focus from territorial competitiveness. Financial information reported to the Superintendencia de Sociedades was used, which was classified into five major regions of the country. It was found that the Amazon region has difficulty obtaining long-term financing, the highest EBITDA and increased cash generation capability found in the Andean region, and finally, the Caribbean has the highest operational cycle and lower profitability, affecting its competitiveness